Program Bantu Perkiraan Hasil Panen Tanaman Jagung Berbasis Web Studi Kasus: Kelompok Tani Mutiara Desa Maunggal Karya - Lasut, Reggy Charles Imanuel; Oslan, Yetli; Wibowo, Argo (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This thesis discusses the challenges encountered by the Mutiara Farmer Group during the corn crop production process. The group faces field-related factors that affect corn production. To estimate crop yields, the group still relies on a manual prediction method, which often leads to estimation errors that can harm its members. Additionally, the lack of planning and preparation in managing corn crops poses a significant problem. This research presents a web-based program for estimating corn crop yields using the Tsukamoto Fuzzy method. The program utilizes factors in the field to assist farmer groups in planning corn planting with expected results. The results indicate that the system can predict crop yields with a high degree of accuracy, as demonstrated by a MAPE(Mean Absolute Percentage Error) value of 15.92%.